2016
DOI: 10.1097/qai.0000000000001072
|View full text |Cite
|
Sign up to set email alerts
|

Disparities Within the Disparity—Determining HIV Risk Factors Among Latino Gay and Bisexual Men Attending a Community-Based Clinic in Los Angeles, CA

Abstract: Background Latino gay, bisexual, and other men who have sex with men (MSM) in the United States have a 50% greater incidence of HIV when compared to White MSM. Previous studies have analyzed factors contributing to condomless anal intercourse (CAI) among Latino MSM, but few studies have followed cohorts of HIV-negative Latino MSM to determine circumstances for HIV infection. Informed by Syndemics Theory, we examine behavioral, biological, and contextual factors associated with HIV infection for Latino MSM. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…We demonstrate that being a recent victim of IPV during the follow-up period was an important contributor to the increased incidence of HIV among MSM. This is in accordance with a previous finding that experiencing IPV during one’s lifetime was associated with a subsequent HIV infection 26 . It also confirms that IPV is an important predictor of HIV incidence, with both short-term and long-term effects, and more emphasis needs to be put on mitigating its negative impact on the HIV epidemic in the MSM population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We demonstrate that being a recent victim of IPV during the follow-up period was an important contributor to the increased incidence of HIV among MSM. This is in accordance with a previous finding that experiencing IPV during one’s lifetime was associated with a subsequent HIV infection 26 . It also confirms that IPV is an important predictor of HIV incidence, with both short-term and long-term effects, and more emphasis needs to be put on mitigating its negative impact on the HIV epidemic in the MSM population.…”
Section: Discussionsupporting
confidence: 93%
“…However, the causality between IPV and HIV infection could not be established because of its cross-sectional study design. One single longitudinal study on MSM in the United States reported a long-term direct relationship between lifetime IPV and HIV seroconversion during a 5-year follow-up 26 . In most circumstances, IPV among MSM is a time-varying determinant that may change as a result of changes in partners or partner dynamics 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this systematic review included diverse MSM populations, including international studies in Asia [ 15 , 16 , 17 , 18 , 19 , 20 ], Africa [ 21 , 22 , 23 ], South America [ 24 , 25 ], and Europe [ 26 , 27 ] (41%); Black and Latino persons in the United States [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] (25%); and young adults or adolescents [ 36 , 37 , 38 , 39 ] (13%). Half of studies (50%) used only community-based surveys [ 15 , 16 , 18 , 20 , 21 , 24 , 25 , 28 , 29 , 32 , 35 , 37 , 38 , 40 , 41 , 42 ], 38% ( n = 12) used population-based surveys [ 17 , 19 , 22 , 23 , 26 , 33 , 34 , 36 , 39 , 43 , …”
Section: Resultsmentioning
confidence: 99%
“…These proxies were assessed using self-identified sexual orientation (i.e., heterosexual, gay/homosexual, bisexual, or not sure) or same-sex partners during the previous 12 months or lifetime. In total, 9% ( n = 3) [ 34 , 43 , 46 ] used proxies exclusively (i.e., sexual identity or partner gender), 82% ( n = 26) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 ] used sexual risk behaviors and did not rely on proxy measures, and 9% ( n = 3) [ 24 , 30 , 31 ] used a combination of these measures to evaluate HIV transmission among MSM.…”
Section: Resultsmentioning
confidence: 99%
“…IPV victimization was associated with higher partner PrEP importance, and experiencing IPV was a significant factor associated with higher partner persuasion to use PrEP, even after adjusting for self-PrEP use perceptions. IPV victimization has commonly been associated with less engagement in HIV prevention activities such as condom use [46, 47] and higher HIV incidence [48]. These results suggest it is possible that IPV may interact very differently with indications of PrEP-related social control relative to other HIV prevention methods.…”
Section: Discussionmentioning
confidence: 99%